1990
DOI: 10.1128/aem.56.7.2046-2050.1990
|View full text |Cite
|
Sign up to set email alerts
|

Fuel alcohol production: effects of free amino nitrogen on fermentation of very-high-gravity wheat mashes

Abstract: Although wheat mashes contain only growth-limiting amounts of free amino nitrogen, fermentations by active dry yeast (Saccharomyces cerevisiae) were completed (all fermentable sugars consumed) in 8 days at 20°C even when the mash contained 35 g of dissolved solids per 100 ml. Supplementing wheat mashes with yeast extract, Casamino Acids, or a single amino acid such as glutamic acid stimulated growth of the yeast and reduced the fermentation time. With 0.9% yeast extract as the supplement, the fermentation time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
66
2
6

Year Published

1992
1992
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(80 citation statements)
references
References 18 publications
6
66
2
6
Order By: Relevance
“…Ethanol energy balance data must be compiled in more detail to better understand differences between corn and other small grains, such as barley, durum, and wheat. Other grain constituents such as lipids (Murthy et al 2006) and free amino nitrogen (Thomas and Ingledew 1990) influence fermentation efficiencies and need to be explored further. Specifically, high levels of the free amino nitrogen in grain can increase yeast fermentation without having to add an artificial nitrogen source (Thomas and Ingledew 1990).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethanol energy balance data must be compiled in more detail to better understand differences between corn and other small grains, such as barley, durum, and wheat. Other grain constituents such as lipids (Murthy et al 2006) and free amino nitrogen (Thomas and Ingledew 1990) influence fermentation efficiencies and need to be explored further. Specifically, high levels of the free amino nitrogen in grain can increase yeast fermentation without having to add an artificial nitrogen source (Thomas and Ingledew 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Other grain constituents such as lipids (Murthy et al 2006) and free amino nitrogen (Thomas and Ingledew 1990) influence fermentation efficiencies and need to be explored further. Specifically, high levels of the free amino nitrogen in grain can increase yeast fermentation without having to add an artificial nitrogen source (Thomas and Ingledew 1990). Reduced starch lipids may be beneficial in increasing the rate of starch conversion to ethanol and it has been shown that the wheat Hardness locus (Ha) is linked to free polar lipid levels in wheat; soft wheats (Ha) have more polar lipid than hard wheats (ha) (Morrison et al 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Although yeast itself does not produce exoproteases during the normal fermentation process, addition of proteinases during mashing or the SSF process nevertheless can generate favorable results (increasing the fermentation rate, cell tolerance to ethanol, and final ethanol yield). Hydrolysis of proteins in the raw materials might help with the release of more starch granules from the protein matrix and increase FAN content in the mash (Thomas and Ingledew 1990;Pérez-Carrillo et al 2008), which will facilitate yeast growth and increase the ethanol fermentation rate and efficiency.…”
Section: Effect Of Protein Digestibility On Ethanol Productionmentioning
confidence: 99%
“…Germination of sorghum could activate intrinsic enzymes in sorghum seeds, facilitating the breakdown of starch and protein matrices, and resulting in increased levels of monosaccharides, oligosaccharides, and free amino acids. Free amino acids are essential nutrients for yeast growth and are beneficial to ethanol fermentation (Taylor 1983;Thomas and Ingledew 1990;Ratnavathi and Ravi 1991). Using germinated sorghum to produce ethanol may have advantages over the normal process using sorghum meals and could achieve higher ethanol yield and fermentation efficiency because of activated intrinsic enzymes, decreased tannin content, and increased starch digestibility in the germinated sorghum.…”
mentioning
confidence: 99%